IDENTITY AND DISSOCIATIVE PROCESS - MIKAELYAN, VLADIMIR (Bulletin of Yerevan University E: Philosophy, Psychology, 2019)
The personality carries a different “I”, but these different “I” are generally controlled by a single center. Any disorder exposes this multiplicity of sub-personalities, in every disorder, there is a conflict of sub-personalities. The trauma introduces a person into life, a split in the structure of its “internal working models”. These working models are peculiar coping-states of a person, a violation in the structure of which leads to their split, to the loss of their temporal and meaningful interrelation.